GENERATION OF THE MAGMAS OF THE DNIEPER-DONETS PALEORIFT VOLCANICS - Lyashkevich Z.M.; Malyuk B.I. (My University, 1990)
The Dnieper-Donets paleorift (DDR) of Late Devonian age is a typical province of continental, subalkalic and alkalic volcanism that was similar in its principal parameters to the volcanism of classical Cenozoic rift zones. The general trend of variation in chemical composition of the experimentally obtained residual liquids does not quite agree with that for volcanics of the DDR. Views can be supplemented by modeling the fractional crystallization of melts of several different compositions. For modeling, we selected three presumed parent magma compositions: Olivine melilitite, picritic basalt and meymechite.
Keywords: Devonian; Cenozoic; Кайнозой; Cenozoic; Paleozoic::Devonian; Палеозой::Девонская